Notary's Responsibility in Making a Cover Note as a Basis For Disbursement of Consumer Financing at Bank Syariah Indonesia in The Lampung Area - Maturohmah, Nur Naim (Jurnal Konstatering, 2025)
A notary is a public official who is authorized to make authentic deeds and has other authorities regulated in a special law, namely the Notary Law. A notary can make a statement letter in the process of providing financing by a bank which is also called a Cover Note, which is a custom in the banking world as well as being a means of evidence and a reference for both the bank and the notary himself. The contents of the Cover Note consist of what work the notary does, the time period for completing the notary's work. The problems in this study are 1) How is the notary's responsibility in making a Cover Note as the basis for disbursing financing at Bank Syariah Indonesia Lampung Area? 2) What are the legal consequences for the notary for the cover note that has been made for the disbursement of financing at Bank Syariah Indonesia Lampung Area? The research method used is juridical-empirical. While this research is descriptive-analytical. This study aims to determine how the notary's responsibility is in completing his work as stated in the Cover Note and the legal consequences for the notary for the Cover Note that has been issued. The theories used are the Theory of Legal Responsibility and the Theory of Legal Protection. Until now, there has been no specific regulation governing the Notary's obligation to issue a Cover Note so that the Notary can be held personally responsible because it is related to the Notary's reputation risk to the bank, but if the information conveyed in the Cover Note causes a loss, the Notary can be held legally responsible, both civilly and criminally.